Predictive value of admission blood pressure for 3-month mortality in patients undergoing revascularization for critical limb ischemia. Issue 12 (December 2020) - Yannoutsos, Alexandra; Lin, Franck; Billuart, Olivier; Gaisset, Roxane; Sacco, Emmanuelle; Beaussier, Hélène; Buronfosse, Anne; Mourad, Jean-Jacques; Emmerich, Joseph; Lazareth, Isabelle; Priollet, Pascal
Abstract : Objective: In patients with critical limb ischemia (CLI), blood pressure (BP) impact on mortality is unknown. We analyzed the predictive value of SBP, DBP and pulse pressure (PP) at hospital admission on 3-month mortality in patients with CLI undergoing revascularization procedure. Methods: From November 2013 to December 2018, 297 consecutive patients were retrospectively included. Admission BP was recorded using automated brachial sphygmomanometer, before revascularization procedure. A median of seven (IQR3–13) separate readings were recorded for each patient and the average represented patient's mean BP (mBP). Clinical and biological parameters were recorded at baseline. Results: The cohort included 163 men (55%) and 134 women (45%) with a mean age of 77.7 ± 11.9 years. Treated hypertension and diabetes were present in, respectively, 62 and 48% of patients. Mean SBP, DBP and PP were 132 ± 18, 70 ± 8 and 62 ± 16 mmHg. Thirty-four patients (11.4%) died during 3-month follow-up, mostly from cardiovascular causes. In univariate analysis, age, female sex, brain natriuretic peptide and C-reactive protein were positively correlated with mortality. BMI, mSBP, mDBP, mPP, hemoglobin, serum albumin and statin treatment were negatively correlated with mortality. In single-pressure multivariate analyses, mSBP ( P = 0.024) and mPP ( P = 0.030) were negatively correlated with mortality. Association between mSBP and mortality had an asymptotic curve pattern and SBP level 135 mmHg or less was significantly correlated with mortality. Conclusion: In patients undergoing revascularization for CLI, admission SBP is an independent predictor for short-term mortality with a negative relationship. SBP level 135 mmHg or less represents a warning sign to explore and correct associated comorbidities.